Phytoremediation of Toxic Metals by Brassica Juncea and Its Effects on Plant’s Antioxidant Potential - Muhammad Jahangir; Hafiz Muhammad Faizan Haider; Dawood Ilyas Minhas (International Journal of Phytomedicine, 2019)
Plants are good source to adsorb metals from soil, water for irrigation and environmental pollution. Toxic industrial effluents are a major source in Pakistan who contaminates food crops. The load of toxic metals in plants not only acts as source of toxicity for its consumer but at the same time affect the nutritional value of the crop. Plants are good source of antioxidants and save us from different diseases ranging from bacterial infection to cancer when consumed. But the antioxidant potential certainly disturbed if they are contaminated with these toxic metals. To check this effect on antioxidant potential we designed this study where we grow Brassica Juncea (common name: Indian Mustard) in botanical garden of our University and fed them with controlled concentration of three metals i.e. Cu, Ni and Cd. We study biosorption potential of these plants for four months starting from germination to a mature plant and also study the antioxidant potential of controlled (fed with ground water) compared to the four month old plant (fed with toxic metals along with ground water). The results of heavy metals analyzed on FAAS show a steady increase in metal sorption of Cu and Ni with increase in concentration and time, however the cadmium adsorption found below detection limit in each case. The antioxidant potential evaluated through “ferric reducing antioxidant power” (FRAP assay), “phosphomolebednum assay” and “Total Phenolic Content” (TPC) show a depletion in antioxidant potential with increase in metal uptake. Thus the antioxidant potential may also be a direct measure of adsorb metal in plant. These values when accumulated in water can cause harm to plants that will become source of different diseases. The values of the antioxidant potential in Brassica Juncea were found high in Blank as compared to that in G-3. This decreased antioxidant potential may be due to the accumulation of metals in plants of group G-3.